Towards a new approach in the teaching of the Holy Qur’an - Tahraoui, Ramdane; Merah, Souad (Center for Promoting Ideas (CPI), USA, 2017)
From the early days of Islam, dynamics of Islamic education in the entire Muslim world have always been associated with the teaching of the holy Qur’an. At the basic elementary level, institutions which provided Qur’an education were often supervised by the ruling authorities, private charitable philanthropists, or pious and people. This educational experience offers a fertile field for those who want to take a closer look at the Islamic education instructional and teaching approaches, such as dictation and memorization, through which the instructor is the only one who explains and analyzes, and the learners’ passive role is relegated in most of the cases to the mere acceptance of what the teacher says. Because a big part of the curriculum, pedagogical programs, and scientific heritage of Qur’an education are in practical oblivion, the researchers are going to review the major approaches of Quran education, and their utility in the 21st century educational arena, then propose ’what is to be done’ to overcome the shortcomings of the traditional methods.